The politics of deregulation - Derthick, Martha; Quirk, Paul J., 1949-; Brookings Institution (Washington, D.C. : Brookings Institution, 1985)
The standard wisdom among political scientists has been that ""iron triangles"" operated among regulatory agencies, the regulated industries, and members of Congress, all presumably with a stake in preserving regulation that protected the industries from competition. Despite almost unanimous agreement among economists that such regulation was inefficient, it seemed highly unlikely that deregulation could occur. Yet between 1975 and 1980 major deregulatory changes that strongly favored competition did take place in a wide range of industries. The results are familiar to airline passengers, user.
4. The Strength of the Reform Forces in Congress -- Reform Victories -- Leadership for Reform -- Reform Advocacy in Congress -- Conclusion -- 5. The Industries' Retreat -- Airlines and Trucking -- Telecommunications -- Conclusion -- 6. The Limits of Deregulation -- Natural Gas Pricing -- Air Pollution -- Davis-Bacon Act -- Milk Marketing -- The Maritime Industry -- 7. The Politics of Ideas -- The Explanation of Success -- The Role of Analysis -- The U.S. Political System -- Index -- A -- B -- C -- D -- F -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Deregulation -- United States; Industrial policy -- United States; Politique industrielle -- États-Unis.; POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Structural Adjustment; BUSINESS & ECONOMICS -- Development -- General; Industrial policy; Deregulation; United States; Staat; Wirtschaft; Regulierung; Industriepolitik; Geschichte; Deregulierung; USA; Industriepolitiek; Bestuursrecht; Déréglementation -- États-Unis.; BUSINESS & ECONOMICS / Business Law